2019
DOI: 10.1111/jcpp.13162
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of family‐focused treatment for child depression compared to individual psychotherapy: one‐year outcomes

Abstract: Objective: Childhood-onset depression is associated with increased risk of recurrent depression and high morbidity extending into adolescence and adulthood. This multisite randomized controlled trial evaluated two active psychosocial treatments for childhood depression: family-focused treatment for childhood depression (FFT-CD) and individual supportive psychotherapy (IP). Aims were to describe effects through 52 weeks postrandomization on measures of depression, functioning, nondepressive symptoms, and harm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Results from the present study can also be considered within the growing literature supporting the value of family-focused and family centered treatments for youth mood disorders (Asarnow et al, 2019;Diamond et al, 2002Diamond et al, , 2003Israel & Diamond, 2013;Miklowitz & Goldstein, 1997;Miklowitz et al, 2020;O'Donnell et al, 2020;Shaw et al, 2009;Tompson et al, 2017;Tompson et al, this issue;Zisk et al, 2019), as well as more individually focused treatments that address parentchild relationships (Mufson et al, 2004;Young & Mufson, 2003). These treatments focus on intervention strategies such as enhancing family support, decreasing family conflict, improving family communication and problem-solving, enhancing parenting skills, and increasing parent motivation to engage in treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Results from the present study can also be considered within the growing literature supporting the value of family-focused and family centered treatments for youth mood disorders (Asarnow et al, 2019;Diamond et al, 2002Diamond et al, , 2003Israel & Diamond, 2013;Miklowitz & Goldstein, 1997;Miklowitz et al, 2020;O'Donnell et al, 2020;Shaw et al, 2009;Tompson et al, 2017;Tompson et al, this issue;Zisk et al, 2019), as well as more individually focused treatments that address parentchild relationships (Mufson et al, 2004;Young & Mufson, 2003). These treatments focus on intervention strategies such as enhancing family support, decreasing family conflict, improving family communication and problem-solving, enhancing parenting skills, and increasing parent motivation to engage in treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Dong et al (2020) show that a Transdiagnostic Sleep and Circadian Intervention can improve some measures of sleep and circadian functioning in adolescents compared with an active control condition involving education about sleep and health. Finally, Asarnow et al (2020) compared a family‐focused treatment targeting childhood depression with individual psychotherapy; the family‐focused treatment resulted in a more rapid easing of depressive symptoms, although there were no long‐term differences in outcome between the two groups.…”
mentioning
confidence: 99%
“…One study found that traditional parent training was as effective as individual CBT in reducing depression among treatment-seeking youths with a depressed caregiver (Eckshtain, Kuppens, & Weisz, 2017). Another study, comparing family-focused treatment for child depression with individual psychotherapy, found evidence that family-focused treatment was associated with parents’ improved understanding of how to manage their children's depression and how to help their children at home (Tompson, Sugar, Langer, & Asarnow, 2017), even though the treatments were similarly effective for youth depression at 1-year follow-up (Asarnow et al, 2020). Many CBT protocols encourage transmission of treatment information to parents via parent handouts, check-ins at the end of therapy sessions, or designated therapy sessions for the parents.…”
Section: Family-level Riskmentioning
confidence: 99%